Interview of Stephen Barnes by Brian Shoemaker - Barnes, Stephen (Byrd Polar Research Center Archival Program, 2005)
Alan Shapley, pp. 11-12, 31 Lawrence Gould, pp. 12-13 Charles Bentley, seismologist, pp. 13, 21-22, 29 Admiral George Dufek, p. 15 Tom Jones, ionospheric specialist, pp. 14-15, 31-32 Bert Crary, Station Scientific Leader at Little America, pp. 15-16, 52 Joel Campbell, inspector of geomagnetic installations in Antarctica, pp. 15-16 Gus Shinn, pilot, p. 17 George Tony, pp. 17-18 Dr. Ruseski, Officer in charge of the Navy contingent, p. 21 “Mildred” Noble, the single woman at the Byrd Station for Operation Deepfreeze II, p. 21 Bill Long, glaciologist, pp. 21, 24, 28-30, 32 Jack Long, IGY mechanic, pp. 22, 24, 29 Len LeSchack, seismologist, pp. 25-26 Fred Darling, meteorological engineer, p. 26 Marion Todd, aurora physicist, pp. 27 Norman Peters, meteorologist, pp. 27-28 Marion Todd, auroral physicist, p. 27 Norman Peters, meteorologist, pp. 27-28 John Annexstad, glaciologist, pp. 29-30 Lloyd Berkner, ionospheric specialist, pp. 31-32 Harry Wexler, ionospheric specialist, pp. 13, 31-32 James Van Allen, p. 32 C. Gordon Little, pp. 37-40, 47, 49 Harry Sellery, ionospheric scientist, pp. 31, 40 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Stephen_Barnes_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Stephen_Barnes_2.mp3 Stephen Barnes, born in 1915 in Philadelphia, described himself as “a very simple type of person.” He earned a Bachelor of Science degree in Secondary Education at West Chester University, and played professional baseball for several years prior to serving in World War II as a navy radar man. After the war, his expertise in electronics brought him to the National Bureau of Standards, and he served in various overseas locations, including three years installing an ionosphere station on Palmyra Island. On one occasion he was severely burned when a midnight fire destroyed his residence; another time a tidal wave destroyed much of the island. His experience as a ham radio operator was essential in ...